2017
DOI: 10.1080/16549716.2017.1383724
|View full text |Cite
|
Sign up to set email alerts
|

Integrating family planning services into HIV care: use of a point-of-care electronic medical record system in Lilongwe, Malawi

Abstract: Background: Integrating family planning (FP) services into human immunodeficiency virus (HIV) clinical care helps improve access to contraceptives for women living with HIV. However, high patient volumes may limit providers’ ability to counsel women about pregnancy risks and contraceptive options. Objectives: To assess trends in the use of contraceptive methods after implementing an  electronic medical record (EMR) system with FP questions and determine the reasons for non-use of contraceptives among women of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…More succinct measures of fertility intentions, such as those used to inform this study’s assessment of unmet need, are demonstrably reliable in predicting pregnancy outcomes [8,17,41] and may be more readily integrated into clinical practice to evaluate the immediate family planning needs of women living with HIV. In one high-volume facility in Malawi, integration of a short family planning assessment using an electronic medical record-based tool prompted healthcare workers to more routinely offer contraceptives during HIV care visits, increasing contraceptive prevalence over a four-year period [42].…”
Section: Discussionmentioning
confidence: 99%
“…More succinct measures of fertility intentions, such as those used to inform this study’s assessment of unmet need, are demonstrably reliable in predicting pregnancy outcomes [8,17,41] and may be more readily integrated into clinical practice to evaluate the immediate family planning needs of women living with HIV. In one high-volume facility in Malawi, integration of a short family planning assessment using an electronic medical record-based tool prompted healthcare workers to more routinely offer contraceptives during HIV care visits, increasing contraceptive prevalence over a four-year period [42].…”
Section: Discussionmentioning
confidence: 99%
“…Pilot studies in Malawi, Kenya, Tanzania, Swaziland, Nigeria, South Africa, and Uganda have shown that this is acceptable, feasible and cost-effective [1216]. In 2011, the Malawi HIV programme integrated family planning into HIV care and treatment services in all ART facilities [17,18]. However, the integrated system is challenged by insufficient policy enforcement, infrastructure, funding and leadership [18].…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, the Malawi HIV programme integrated family planning into HIV care and treatment services in all ART facilities [17,18]. However, the integrated system is challenged by insufficient policy enforcement, infrastructure, funding and leadership [18].…”
Section: Introductionmentioning
confidence: 99%
“…Women living with HIV theoretically should have ongoing contact with their health care system, and this routine engagement may improve access to contraception counseling and services, resulting in increased contraceptive utilization. 37,38 Previous studies (as well as this study) have found evidence in support of coupling HIV treatment services and contraception counseling 37,38 ; however, the benefits and challenges of comprehensive women's health care in global settings are not fully understood and warrant further examination. For example, a recent study from South Africa found women living with HIV (these are women who are likely to be engaged in health care) were more likely to have an unplanned pregnancy than their uninfected peers, which is both surprising and worrisome.…”
Section: Discussionmentioning
confidence: 72%